Inflammatory cytokine response is greater in acute tibial plafond fractures than acute tibial plateau fractures. Issue 12 (24th April 2017) - Haller, Justin M.; Marchand, Lucas; Rothberg, David L.; Kubiak, Erik N.; Higgins, Thomas F.
ABSTRACT: The purpose of the study was to compare the inflammatory cytokine and matrix metalloproteinase (MMP) concentrations in synovial fluid after acute plafond fracture with acute tibial plateau fracture. Between December 2011 and August 2014, we prospectively enrolled patients with acute tibial plateau and plafond fractures. Synovial fluid aspirations were obtained from injured and uninjured joints. The concentrations of IL‐1β, IL‐1RA, IL‐6, IL‐8, IL‐10, MCP‐1, TNF‐α, MMP‐1, ‐3, ‐9, ‐10, ‐12, and ‐13 were quantified using multiplex assays. A Bonferroni correction was used so that the adjusted alpha level for significance was p  < 0.004. We enrolled 45 tibial plateau fractures and 19 plafond fractures. Mean patient age was 42 years (range, 20–60) and 64% were male patients. There were 24 low‐energy (OTA 41B) plateau fractures and eight low‐energy (OTA 43B) plafond fractures. There were 21 high‐energy (6 OTA 41B3 and 15 OTA 41C) plateau fractures and 11 high‐energy (OTA43C) plafond fractures. All cytokines and MMPs except MMP‐13 were significantly elevated in plafond fractures compared to uninjured ankles. When comparing acutely injured joints, IL‐8 ( p  < 0.001), IL‐1β ( p  = 0.002), and MMP‐12 ( p  = 0.001) were significantly higher in plafond fractures compared to plateau fractures. Concentrations of IL‐1RA ( p  = 0.008) and MCP‐1 ( p  = 0.005) were higher in plafond fractures, and MMP‐10 ( p  = 0.01) was higher in plateau fractures, but these differences did not reach significance. In conclusion, several cytokines and MMPs were significantly elevated in acute plafond fractures as compared to acute tibial plateau fractures. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2613–2619, 2017.